ChemInform Abstract: Regiocomplementary Cycloaddition Reactions of Boryl‐ and Silylbenzynes with 1, 3‐Dipoles: Selective Synthesis of Benzo‐Fused Azole Derivatives. Issue 33 (25th July 2013) - Ikawa, Takashi; Takagi, Akira; Goto, Masahiko; Aoyama, Yuya; Ishikawa, Yoshinobu; Itoh, Yuji; Fujii, Satoshi; Tokiwa, Hiroaki; Akai, Shuji
Abstract In the presence of iPr‐MgCl, 3‐borylbenzynes which are generated efficiently from new borolanes of type (I) undergo regiospecific, electrostatically controlled [3 + 2] cycloaddition with 1, 3‐dipoles to afford proximal cycloadducts such as (III) and (VI).